Pengaruh Karakteristik Individu dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. MNS (Multi Nabati Sulawesi) Bitung - Mutiarawati Saliding; William A. Areros; Wehelmina Rumawas (Universitas Sam Ratulangi, 2019)
The progress of the company was not the eye of the eye located on how much profit they were by, but it is also in human resources to form in a company to be established to be paranoid to be well eployess well based on justice or company policy considering humanity values, work achievement, education, and work experience.This research is aiming to know the Individual Characteristics and Work Environment to Employee Performance. Research that located at PT. Multi Nabati Sulawesi Bitung. The sample taken was 112 people from a total 450 employees in the company. In this study are using simple statistics with a simple regression with the SPSS version 23.00 to test the significant connection between variables and to measure the glory of the influence that occurs on variation of Individual Characteristics and Work Environment to Employee Performance. Based on the calculations of using the SPSS 23.00 software device that’s a variable Individual Characteristics of affects the employee performance variables which show that Work Environment received is not in accordance with the expectation and desires of employees, so that there is a coplaint for every employee in the company